2019
DOI: 10.1002/trtr.1806
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Social Studies and English Language Arts: Digital Stories and the Revolutionary War

Abstract: Based on research conducted in a fourth‐grade classroom, the author describes one teacher's process for integrating social studies and English language arts using a writers’ workshop approach. Furthermore, the fourth‐grade teacher was able to provide students with an opportunity to engage in multimodal composition. After conducting research independently and collaboratively, the students wrote scripts, located images, and recorded narration to create digital stories from the perspective of a Revolutionary War … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Over three-quarters of the instructors also agreed that the use of multimodal digital literacy practices in 21st-century classrooms is essential. The acknowledgment of the value of multimodality is consistent with previous studies [24], [34]- [37], where it was found that appropriate employment of multimodal digital literacy methodologies and resources serves as an optimal intersemiotic complementarity in teaching and learning.…”
Section: Discussionsupporting
confidence: 88%
“…Over three-quarters of the instructors also agreed that the use of multimodal digital literacy practices in 21st-century classrooms is essential. The acknowledgment of the value of multimodality is consistent with previous studies [24], [34]- [37], where it was found that appropriate employment of multimodal digital literacy methodologies and resources serves as an optimal intersemiotic complementarity in teaching and learning.…”
Section: Discussionsupporting
confidence: 88%
“…Çünkü dijital hikâye anlatımının disiplinlerarası kullanımı öğrenciler için ilgi çekici bulunurken zamanı akıllıca kullanmaya ve konulara ilişkin genel ve kapsamlı bir yaklaşım sergilemeye ilişkin olumlu bir katkı sağladığı değerlendirilmektedir (Pavlou, 2020). Disiplinlerin dijital hikâye anlatımının multimodal formatında entegrasyonu, derin içerik öğrenimi olanaklarını genişletebilmekte ve öğrencileri yazar olarak konumlandırabilmektedir (Yearta, 2019). Alanyazında teknolojinin, sosyal bilimler disiplinleri için potansiyel bir itici güç olduğu fakat bu potansiyelin yeteri kadar ortaya çıkarılmadığı değerlendirilmektedir (Manfra, 2014).…”
Section: Sonuç Ve Tartışmaunclassified
“…Digital Storytelling (DST) refers to a project-based instruction in which students work in groups to research the topic they choose and then make a short video clip to present what they have found in the form of storytelling. In this study, the researcher designed the project-based instruction by adapting Yearta's (2019) DST framework.…”
Section: Definitions Of Termsmentioning
confidence: 99%
“…The most recent one among them is from Yearta (2019). Yearta (2019) proposed a framework of DST, which includes:…”
Section: Dst Instructional Frameworkmentioning
confidence: 99%
See 1 more Smart Citation